Problem-solving and creative thinking skills with the PBL model: The concept of the human circulatory system - Leasa, Marleny; Fenanlampir, Albertus; Batlolona, John Rafafy; Saimima, Abdul Salam (Universitas Negeri Jakarta, 2021)
Science learning in elementary schools using the PBL learning model can grow students' higher-order thinking skills, such as problem-solving and creative thinking skills. The purpose of correlational research was to analyze the relationship between problem-solving and creative thinking skills of elementary school students through the implementation of PBL. The predictor variables and criteria in the research were in the form of problem-solving and creative thinking skills, respectively. The population of this study was the fifth-grade elementary school students, totaling 120 students. This study’s sample was 33 students. The data retrieval used problem-solving and creative thinking skills tests on the concept of the human circulatory system. The data analysis was performed by linear regression. The results showed a correlation between creative thinking and problem-solving skills in learning with PBL. There is a strong relationship between problem-solving and creative thinking skills through PBL. The predictor variable contributed 37.8% to the criterion variable. This study recommends that it is essential to familiarize PBL in elementary schools learning to improve students' higher-order thinking skills.